An Overview on Molecular Markers in Uterine Aspirates for Non-Invasive Diagnosis For Endometrial Carcinoma Detection - Rithikha Sooriyaprakash, Thirumalai Kumaran Rathinam, Ramanarayana Reddy , Yokesh Shanmugam, Divya Chokkalingam (South Eastern European Journal of Public Health, 2024)
Introduction: This research aims to enhance the diagnostic accuracy of endometrial cancer (EC), a common and debilitating malignancy prevalent among women in developed nations. The rising incidence of EC, attributed to increasing obesity and longevity, necessitates improved diagnostic methods. Traditional invasive procedures like dilation and curettage (D&C) or hysteroscopy, although effective, can cause patient discomfort and variability in diagnosis due to subjective histopathological evaluations. Objectives: To address these limitations, this study explores non-invasive molecular diagnostics, specifically identifying biomarkers in uterine aspirates. Methods: The investigation, conducted at Vall d'Hebron University Hospital, involved collecting uterine aspirates from patients across various EC stages and performing RNA extraction and gene expression analysis to identify potential molecular markers. Results: The study revealed several genes with altered expression in EC tissues, including up regulated genes like ACAA1, AP1M2, CGN, and DDR1, and down regulated genes like DCN and EFEMP2. These findings were validated through techniques like RT-qPCR, immunohistochemistry (IHC), and Western blot analysis, ensuring the reliability of these markers at both RNA and protein levels. Conclusions: Statistical analysis revealed that certain biomarkers, such as SIRT6 and P4HB, demonstrated high diagnostic accuracy with areas under the curve (AUC) approaching 1, indicating their potential to significantly enhance early EC detection, reducing the need for invasive procedures and potentially improving patient outcomes. The study concludes by emphasizing the need for further large-scale validation and clinical integration of these biomarkers, which could revolutionize EC diagnosis and treatment.